Effect of deposit chemistry on microbial community structure and activity: Implications for under-deposit microbial corrosion - Diaz-Mateus, Maria A.; Salgar-Chaparro, Silvia J.; Machuca, Laura L.; Farhat, Hanan (Frontiers in Microbiology, 2023)
This study assessed the impact of sand deposit chemistry on the sessile microbial community structure, metabolic activity rates, functional profile and the resulting risk of under-deposit microbial corrosion of carbon steel. Sand deposits recovered from an oil pipeline were used in their raw form and compared against the same deposits exposed to heat treatment to remove organic compounds. The native microbial consortium in the oilfield deposit was used in the experiments. A range of microbial molecular methods, biostatistics, and bioinformatics tools demonstrated that the raw untreated deposit from the field containing hydrocarbons and treatment chemicals resulted in a more diverse microbial community compared to its treated counterpart. Moreover, biofilms developed in the raw sand deposit exhibited higher metabolic rates, with functional profile analysis indicating a predominance of genes associated with xenobiotics degradation. Uniform and localised corrosion were more severe in the raw sand deposit compared to the treated sand